2005
DOI: 10.1210/jc.2004-1963
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Leptin Correlates with Left Ventricular Mass in Morbid (Grade III) Obesity before and after Weight Loss Induced by Bariatric Surgery: A Potential Role for Leptin in Mediating Human Left Ventricular Hypertrophy

Abstract: Context:Obesity is frequently associated with left ventricular hypertrophy, even when uncomplicated by hypertension or diabetes mellitus. Left ventricular hypertrophy is an important risk factor for congestive heart failure.Objective: The objective of this study was to evaluate the relationship between leptin and left ventricular mass in uncomplicated, morbid (grade 3) obesity and the existence of leptin receptors and intracellular signaling proteins in the human heart. Design: Left ventricular mass (LVM) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 52 publications
5
70
1
3
Order By: Relevance
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy. Furthermore, in patients with CAD16 and acute myocardial infarction,24 a positive association has been reported between circulating leptin levels and markers of LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy. Furthermore, in patients with CAD16 and acute myocardial infarction,24 a positive association has been reported between circulating leptin levels and markers of LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, investigators have related circulating concentrations of adipokines to imaging indices of cardiac remodeling. These prior studies have typically been conducted in small samples, or samples with an overrepresentation of obese individuals or elderly people, and usually focused on a single adipokine 10, 11, 13, 21, 22, 23, 24, 25, 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also to be considered that changes of body weight with both BPD and LGB were quite reduced from the biological point of view. As a matter of fact, leptin, which is known to decrease after significant weight loss, did not change in subjects under study [21].…”
Section: Discussionmentioning
confidence: 74%
“…41 Furthermore, circulating leptin levels correlate well with left ventricular (LV) mass in morbid obesity both before and after bariatric surgery. 49 Adiponectin is among the highest produced adipokines, possessing both anti-inflammatory and antidiabetic properties, although levels are paradoxically decreased in obesity and insulin-resistance states. Early epidemiological data suggest that lower plasma concentrations of adiponectin are associated with the risk of coronary artery disease when adjusted for age and BMI, 43 whereas raised levels reveal a lower risk of myocardial infarction.…”
Section: Adipokines and Bariatric Surgerymentioning
confidence: 99%